Evaluation of In Vivo Toxicity of Biological Nanoparticles. Issue 9 (20th September 2021) - Driscoll, Julia; Yan, Irene K.; Angom, Ramcharan Singh; Moirangthem, Anuradha; Patel, Tushar
Abstract: Biologically derived nanoparticles such as extracellular vesicles are promising candidates for therapeutic applications. In vivo toxicity of biological nanoparticles can result in tissue or organ damage, immunological perturbations, or developmental effects but cannot be readily predicted from in vitro studies. Therefore, an essential component of the preclinical assessment of these particles for their use as therapeutics requires screening for adverse effects and detailed characterization of their toxicity in vivo. However, there are no standardized, comprehensive methods to evaluate the toxicity profile of nanoparticle treatment in a preclinical model. Here, we first describe a method to prepare bovine milk‐derived nanovesicles (MNVs). These MNVs are inexpensive to isolate, have a scalable production platform, and can be modified to achieve a desired biological effect. We also describe two vertebrate animal models, mice and zebrafish, that can be employed to evaluate the toxicity profile of biologically derived nanoparticles, using MNVs as an example. Treatment‐induced organ toxicity and immunological effects can be assessed in mice receiving systemic injections of MNVs, and developmental toxicity can be assessed in zebrafish embryos exposed to MNVs in embryo water. Utilizing these animal models provides opportunities to analyze the toxicity profiles of therapeutic extracellular vesicles in vivo. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of milk‐derived nanovesicles Basic Protocol 2 : In vivo screening for organ toxicity and immune cell profiling using mice Basic Protocol 3 : In vivo developmental toxicity screening using zebrafish